Le barattage des savoirs - Magalie Saussey (Revue d'anthropologie des connaissances)
Shea butter, known as a typical West African product, is nowadays sought-after on the international markets. The speeded-up circulation of nuts and shea butter, in order to supply food and cosmetic industries, has engendered new learning devices in which new norms -principally technical ones - are transmitted and tested, and are supposed to improve the producers’ techniques, so as to get products in accordance with the quality requirements of the international market. This article will analyze the mechanisms of co-production of knowledge that occurs in these training processes promoted by development actors for the improvement of shea butter production in Burkina Faso.